Systematic total arch replacement with thoraflex hybrid graft in acute type A aortic dissection: A single centre experience - Chivasso, Pierpaolo; Mastrogiovanni, Generoso; Bruno, Vito Domenico; Miele, Mario; Colombino, Mario; Triggiani, Donato; Cafarelli, Francesco; Leone, Rocco; Rosapepe, Felice; De Martino, Matteo; Morena, Elvira; Iesu, Ivana; et al. (Frontiers in Cardiovascular Medicine, 2022)
Introduction: In the last two decades a more aggressive approach has been encouraged to treat patient with acute type A aortic dissection, extending the repair to the aortic arch and proximal descending thoracic aorta with the frozen elephant trunk (FET) implantation. Here we report our single centre experience with the FET technique for the systematic treatment of emergency type A aortic dissection. Material and Methods: Between December 2017 and January 2022, 69 consecutive patients were admitted with acute type A aortic dissection; of those, 66 patients (62.9 ± 10.2 years of age, 81.8% men) underwent emergency hybrid aortic arch and frozen elephant trunk repair with the multibranched Thoraflex hybrid graft and were enrolled in the study. Primary end point were 30 days- and in-hospital mortality. Secondary end points were post.operative morbidity and follow up survival. To better clarify the impact of age on surgical outcomes, we have divided the study population into two groups: group A for patients < 70 years of age (47 patients), group B for patients ≥ 70 years (19 patients). Time to event analysis has been conducted using Log-rank test and displayed with Kaplan-Meier curves. A multiple Cox proportional Hazard model was developed to identify predictors of long-term survival with a stepwise backward/forward selection process. Results: Thirty-days- and in-hospital mortality were 10.6 and 13.6%, respectively. Stroke occurred in 3 (4.5%) patients. Two (3.0%) patients experienced spinal cord ischemia. We did not find any statistically significant difference among the two groups in terms of main post-operative outcomes. The multivariable Cox proportional hazard model showed left ventricular ejection fraction (HR: 0.83, 95% CI: 0.79-0.92, p <0.01), peripheral vascular disease (HR: 15.8, 95% CI: 3.9-62.9, p < 0.01), coronary malperfusion (HR: 0.10, 95% CI: 0.01-0.77, p =0.03), lower limbs malperfusion (HR: 5.1, 95% CI: 1.10-23.4, p = 0.04) and cardiopulmonary bypass time (HR: 1.02, 95% CI: 1 – 1.04, p = 0.01) as independent predictors of long term mortality. Conclusions: Frozen elephant trunk repair to treat emergency type A aortic dissection appears to be associated with good early and mid-term clinical outcomes even in the elderly.